ANXIETY AND DEPRESSION IN BURN PATIENTS - Alvi, Tabassum; Assad, Fatima; zeb, Aurang; Malik, M A Nasir (Journal of Ayub Medical College Abbottabad, 2009)
Background: The psychological aspects of burn injury have been researched in different parts of world producing different outcomes. Therefore objective of this research is to determine the frequency of Anxiety and Depression in burn patients. To assess the socio-demographic distribution of patients developing Anxiety and Depression and to determine the effects of burn related factors on development of Anxiety and Depression. Methods: A Case series was conducted at the Department of Burn, Pakistan Ordinance Factory Hospital, Wah Cantt. for a duration of 12 months commencing from June 2007 and concluded in May 2008. The study population comprised of hospitalized patients with 1% to 50%, selected through non probable sampling technique who were assessed for Anxiety and Depression on fifteen day after burn injury. Testing protocol comprised of questionnaire having socio-demographic variables and burn related variables. Beck Depression Inventory and Beck Anxiety Inventory was applied to evaluate Anxiety and Depression in Burn patients. Descriptive statistics like mean with Standard Deviation was calculated for age. Frequencies along with percentages were calculated for socio-demographic variables. The frequencies and proportions were also calculated for presence and extent of severity of depression and anxiety in burn patients. Results: Fifty patients were included in the study, thirty patients (60%) were male and 20 (40%) were females. The mean age of participants was 33.64±19 years. Majority of participants, 38 (76%) had sustained burn injury up to 25%. Flame was found to be most common agent of burn injuries affecting 19 (38%) patients. Depression was seen amongst 29 (58%) patients. Thirteen (26 %) patients had mild, 7 (14%) had moderate and 9 (18%) had severe Depressive symptoms. Anxiety was seen among 41 (82%) patients, thirteen (26%) patients had mild, 11 (22%) had moderate and 17 (34%) had severe Anxiety symptoms. Conclusion: Anxiety was present in 41 (82%) and Depression was present in 29 (58%) patients following burn injury. This study highlights the importance of the simultaneous evaluation and management of Anxiety and Depression in burn injured patients. Keywords: Anxiety, Depression, Burn